Membedah Karakter Leo Menggunakan Psikoanalisis, Kognitif, Dan Psikososial Dalam Novel Kisah Dan Hujan Pun Berhenti - Mario Fransisco Loise Sodho; Kharisa Dira Saputri; Eva Dwi Kurniawan (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This paper aims to present an in-depth psychological analysis of the novel "Kisah dan Hujan Pun Berhenti" by a renowned author. In this work of literature, the author explores the psychological aspects of the main characters who face various issues and conflicts in their lives. This research utilizes various psychological theories to understand the psychological changes of these characters and how they respond to various events in the story. The analysis encompasses character development, internal and external conflicts, mental disorders, and the influence of the environment and weather on the psychological well-being of the characters. Additionally, this paper delves into the symbolism and metaphors that may be contained within the novel, providing additional insights into the psychological aspects of the story. The results of the analysis show that the characters in "Kisah dan Hujan Pun Berhenti" undergo significant changes throughout the narrative, reflecting psychological aspects such as personal growth, inner conflicts, and how they cope with trauma or difficulties. The environment and weather also play a vital role in portraying the characters' emotions and driving the plot. This research offers a deeper understanding of how psychology plays a central role in shaping the narrative and characters in this work of literature. In conclusion, the novel presents the complexity of human life and invites readers to contemplate the psychological aspects of the journey.